A high step-up switched z-source converter (Hs-szc) with minimal components count for enhancing voltage gain - Kumar, R. (MDPI AG, 2021)
Some applications such as fuel cells or photovoltaic panels offer low output voltage, and it is essential to boost this voltage before connecting to the grid through an inverter. The Z-network converter can be used for the DC-DC conversion to enhance the output voltage of renewable energy sources. However, boosting capabilities of traditional Z-network boost converters are limited, and the utilization of higher parts count makes it bulky and expensive. In this paper, an efficient, high step-up, switched Z-source DC-DC boost converter (HS-SZC) is presented, which offers a higher boost factor at a smaller duty ratio and avoids the instability due to the saturation of inductors. In the proposed converter, the higher voltage gain is achieved by using one inductor and switch at the back end of the conventional Z-source DC-DC converter (ZSC). The idea is to utilize the output capacitor for filtering and charging and discharging loops. Moreover, the proposed converter offers a wider range of load capacity, thus minimizing the power losses and enhancing efficiency. This study simplifies the structure of conventional Z-source converters through the deployment of fewer components, and hence making it more cost-effective and highly efficient, compared to other DC-DC boost converters. Furthermore, a comparison based on the boosting capability and number of components is provided, and the performance of the proposed design is analyzed with non-ideal elements. Finally, simulation and experimental studies are carried out to evaluate and validate the performance of the proposed converter. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.